A theory of change roadmap for universal health coverage in India - Angela Chaudhuri; Nilakshi Biswas; Shiv Kumar; Asha Jyothi; Ranjani Gopinath; Nachiket Mor; Preethi John; Thelma Narayan; Mirai Chatterjee; Vikram Patel; Vikram Patel (Frontiers Media S.A., 2022)
The Theory of Change (ToC) approach is one of the methodologies that the Lancet Citizens' Commission has chosen to build a roadmap to achieving Universal Healthcare (UHC) in India in the next 10 years. The work of the Citizens' Commission is organized around five workstreams: Finance, Human Resources for Health (HRH), Citizens' Engagement, Governance, and Technology. Five ToC workshops were conducted, one for each workstream. Individual workshop outputs were then brought together in two cross-workstream workshops where a sectoral Theory of Change for UHC was derived. Seventy-four participants, drawn from the Commission or invited for their expertise, and representing diverse stakeholders and sectors concerned with UHC, contributed to these workshops. A reimagined healthcare system achieves (1) enhanced transparency, accountability, and responsiveness; (2) improved quality of health services; (3) accessible, comprehensive, connected, and affordable care for all; (4) equitable, people-centered and safe health services; and (5) trust in the health system. For a mixed system like India's, achieving these high ideals will require all actors, public, private and civil society, to collaborate and bring about this transformation. During the consultation, paradigm shifts emerged, which were structural or systemic assumptions that were deemed necessary for the realization of all interventions. Critical points of consensus also emerged from the workshops, such as the need for citizen-centricity, greater efficiency in the use of public finances for health care, shifting to team-based managed care, empowerment of frontline health workers, the appropriate use of technology across all phases of patient care, and moving toward an articulation of positive health and wellbeing. Critical areas of contention that remained related to the role of the private sector, especially around financing and service delivery. Few issues for further consultation and research were noted, such as payment for performance across both public and private sectors, the use of accountability metrics across both public and private sectors, and the strategies for addressing structural barriers to realizing the proposed paradigm shifts. As the ToCs were developed in expert groups, citizens' consultations and consultations with administrative leaders were recommended to refine and ground the ToC, and therefore the roadmap to realize UHC, in people's lived reality.